Status Hukum PPJB Berupa Tanah Belum Dipecah yang Dijaminkan Serta Penyelesaiannya Untuk Melindungi Pembeli Dalam Perkara Kepailitan (Studi Putusan Mahkamah Agung Nomor 395 K/PDT.SUS-PAILIT/2024) - Sahetapy, Prilly Priscilia; Irna Nurhayati (Fakultas Hukum Universitas Airlangga, 2025)
This study aims to determine and analyze the legal status of PPJB objects in the form of land that has not been divided in bankruptcy cases according to Indonesian law (Study of Commercial Court Decision Number 28 / Pdt.Sus-Other Claims / PN Niaga Jkt.Pst jo. Supreme Court Decision Number 395 K / Pdt.Sus-Pailit / 2024) and to determine and analyze the settlement of PPJB objects after the Supreme Court Decision Number 395 K / Pdt. Sus-Pailit / 2024 to protect the rights of buyers in bankruptcy cases. This research is descriptive and normative. The main data is secondary data obtained based on library research on laws and regulations, supported by interviews with informants. The method of collecting research data is a documentary study with research tools in the form of written materials and direct communication with research tools in the form of interview guidelines. Then, the research data are analyzed qualitatively and concluded using the deductive method. The results of the study are that the legal status of the PPJB object in the form of land that has not been divided and has been pledged in a bankruptcy case according to Indonesian law is valid because the PPJB is a preliminary agreement when there are obligations that have not been fulfilled to make an AJB, such as dividing the land. The District Court Decision stated that the PPJB object was not listed in the developer's bankruptcy estate list, so it did not consider the PPJB, while the Supreme Court Decision stated that the PPJB was valid because the buyers had acted in good faith. Then, the settlement of the PPJB object after the Supreme Court Decision to protect the buyer's rights in the bankruptcy case was carried out by removing the land and housing units that were the object of the case from the bankruptcy estate list. The next stage is the debtor's debt repayment, partial repayment application, division of building rights title, making AJB, changing names, requesting changes in building use rights to ownership rights, and issuing ownership rights certificates in the names of the buyers. Keywords: Sales and Purchase Agreement, the division of building rights title, settlement of the verdict